Investigating visitor behavior in relation to Leave No Trace practices - Ward, Joseph (Kansas State University, 2023)
Leave No Trace (LNT) has existed since the 1990’s and has been a topic of many studies that examine its effectiveness for influencing visitor behaviors to use minimum impact practices while visiting parks and protected areas (PPAs). Many of those studies rely on visitors reporting their behaviors via surveys but do not utilize observed behavioral data. This study analyzed reported and observed behaviors of visitors using informal social trails. Trail cameras collected observed data which was compared to self-reported survey data. The study area was Tuttle Creek State Park because State Parks are understudied areas within LNT research compared to other types of PPAs. Moreover, this research examined various types of social trails and their usage to gain a robust understanding of how LNT principles influence visitor behaviors. Preliminary results show approximately 40% of visitors who self-reported that they did not use a social trail were photographed by cameras while using non-designated trails. There is the potential that future research on LNT should rely more on observed visitor behaviors or to use that data in collaboration with self-reported behaviors.
Keywords: Visitor behaviors; Leave No Trace; Social trails; Observational data